Titanium Carbide (Ti3C2Tx) MXene as Efficient Electron/Hole Transport Material for Perovskite Solar Cells and Electrode Material for Electrochemical Biosensors/Non-Biosensors Applications - Theophile Niyitanga; Archana Chaudhary; Khursheed Ahmad; Haekyoung Kim (Micromachines, 2023)
Recently, two-dimensional (2D) MXenes materials have received enormous attention because of their excellent physiochemical properties such as high carrier mobility, metallic electrical conductivity, mechanical properties, transparency, and tunable work function. MXenes play a significant role as additives, charge transfer layers, and conductive electrodes for optoelectronic applications. Particularly, titanium carbide (Ti3C2Tx) MXene demonstrates excellent optoelectronic features, tunable work function, good electron affinity, and high conductivity. The Ti3C2Tx has been widely used as electron transport (ETL) or hole transport layers (HTL) in the development of perovskite solar cells (PSCs). Additionally, Ti3C2Tx has excellent electrochemical properties and has been widely explored as sensing material for the development of electrochemical biosensors. In this review article, we have summarized the recent advances in the development of the PSCs using Ti3C2Tx MXene as ETL and HTL. We have also compiled the recent progress in the fabrication of biosensors using Ti3C2Tx-based electrode materials. We believed that the present mini review article would be useful to provide a deep understanding, and comprehensive insight into the research status.